EFFECTS OF AN APPLICATION OF SELF-EFFICACY THEORY WITH MINDFULNESS TO REDUCE STRESS LEVELS IN UNDERGRADUATE STUDENTS THROUGH THE "CALM SATI, CUTS STRESS" PROGRAM - มือขุนทด, ชนะ; หีบแก้ว ปัดชาสุวรรณ์, นาฏนภา; บุญทศ, ขวัญสุดา; ตัญตรัยรัตน์, พฤกษ์ (Primary Health Care Journal (Northeastern Edition), 2026)
Mental health is a widespread problem globally, especially among the 18-25 age group, which is the typical age of undergraduate students. This research aimed to study the effect of applying self-efficacy theory combined with mindfulness training to reduce stress levels in undergraduate students through the "Calm Sati, Cuts Stress" program. The sample consisted of 54 students, divided into an experimental group of 26 students and a control group of 28 students. The experimental group participated in activities based on the components of self-efficacy theory for 10 weeks. Data on self-efficacy in mindfulness, mindfulness level, and stress level were collected. Data were analyzed using analysis of covariance (ANCOVA) to compare differences between groups, controlling for pre-test scores and cumulative grade point average as co-variables. The statistical significance level was set at 0.05. The research results showed that, when controlling for pre-test scores and cumulative grade point average, The adjusted mean scores of mindfulness self-efficacy (F (1, 51) = 0.02, p = 0.90), mindfulness (F (1, 51) = 0.15, p = 0.70), and stress (F (1, 51) = 3.16, p = 0.08) between the experimental and control groups did not differ significantly. The results indicate that the short-term “Calm Sati, Cuts Stress” program did not show empirical effects on changes in mindfulness self-efficacy, mindfulness and stress levels among undergraduate students. However, the integration of self-efficacy theory with mindfulness training still has the potential to develop a mental health promotion program in the educational context. It may be necessary to increase the duration, frequency, and intensity of the training to achieve clearer results in the future.